Morphological Evidence Supports the Taxonomic Reinstatement of the Endemic Chinese Species Iris pandurata (Iridaceae) by Segregation from I. tigridia - Eugeny V. Boltenkov (Plants)
Unfortunately, the statuses of the numerous names of the genus Iris at specific rank remain unresolved. This study considers I. pandurata, the species that was first described in 1880 and then 30 years later and is, however, still synonymized with I. tigridia. The morphological relationship between these two species and I. trippneriana, a previously unplaced name, has been assessed here. The morphological analysis has revealed that I. pandurata and I. trippneriana are actually a single species that can easily be distinguished from I. tigridia by the rhizome shape, the adventitious roots shape, the flowering stem structure, and the falls ornamentation. The results support the reinstatement and recognition of I. pandurata at specific rank, including I. trippneriana as a synonym. Being endemic to China, I. pandurata has a narrow distribution range in the Qilian Mountains in the Gansu and Qinghai provinces. This report provides an updated nomenclature for I. pandurata, including I. tigridia, detailed photographs of living plants to facilitate identification, images of type specimens, a list of specimens examined, and comments on their distributions and habitats. A lectotype for I. trippneriana is designated here.